Microplastic pollution in lower Cimandiri River, Indonesia: early detection on the occurrence, abundance and distribution. Issue 1 (1st July 2022) - Henny, C; Triyanto,; Suryono, T; Rohaningsih, D; Yoga, G P; Waluyo, A
Abstract: Increasing in production and use of synthetic plastic materials constantly are responsible for the global increase in plastic debris in freshwater environments especially rivers. River is believed to be one of the important way to transport microplastics from inland to the Ocean. The study was conducted to assess early detection of the occurrence, abundance and distribution of microplastics (MPs) in lower Cimandiri River, West java, Indonesia, in which its water flows to the Indian Ocean. The water and sediment samples were collected in September 2020 from seven sampling sites in the upstream river tributaries, in the downstream segments and in the estuary. The analyses were done using a monocular stereo microscope in the laboratory. Preliminary detection showed that the abundance of microplastics was as high as 96 - 325 particles/m 3 in the water and 620 - 950 particel/kg in the sediment of Lower Cimandiri River. Fibers accounted for > 70 % of the MPs types, and the size of < 300 mμ was the dominant MPs found (> 60%). Predominated small size MPs could pose a threat to the eels population sustainability. High MPs detected in Lower Cimandiri River could be a potential source of MPs pollution to the Indian Ocean.